2018
DOI: 10.1177/1362361318778286
|View full text |Cite
|
Sign up to set email alerts
|

Autistic people’s perspectives on stereotypes: An interpretative phenomenological analysis

Abstract: Autism stereotypes can often portray autistic people in a negative way. However, few studies have looked at how autistic people think they are perceived by others, and none have specifically asked autistic people what they think the autistic stereotypes are. Semi-structured interviews with twelve autistic adults (aged between 20-63 years) were conducted. Using Interpretative Phenomenological Analysis, three main themes emerged from the data. These were: (1) primary stereotype is that autistic people are 'weird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 82 publications
(102 reference statements)
2
23
0
Order By: Relevance
“…Due to the social communication problems, which are inherent to ASD, this social construction of knowledge seems specifically difficult for adolescents with ASD. In turn, this difficulty might be one of the reasons why persons with ASD often indicate that they feel that others stereotype them as being "weird or stupid" [53], as they feel a lack of knowledge or insight. For adolescents in this study, using public transport was an overall pleasant experience.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the social communication problems, which are inherent to ASD, this social construction of knowledge seems specifically difficult for adolescents with ASD. In turn, this difficulty might be one of the reasons why persons with ASD often indicate that they feel that others stereotype them as being "weird or stupid" [53], as they feel a lack of knowledge or insight. For adolescents in this study, using public transport was an overall pleasant experience.…”
Section: Discussionmentioning
confidence: 99%
“…Most widely used was a form of credibility checking by asking participants to give feedback on researcher interpretations. All but one study (Treweek et al, 2018) employed this technique. Credibility checking is a common technique of validation within qualitative research, but in the context of autism studies, it carries a new significance.…”
Section: Attention To Power Relationsmentioning
confidence: 99%
“…Other techniques were employed by seven studies in addition to credibility checking, with the exceptionof Treweek et al, 2018).As described, MacLeod et al (2013; entered into a further dialogue with participants in relation to draft publications, allowing participants the opportunity for further reflection and commentary from a temporal distance -an opportunity which only a minority took. Five studies involved autistic stakeholders who were not participants, two of which used the formal Patient and Public Involvement (PPI) process in the planning stages(Casement, Carpio de los Pinos & Forrester-Jones, 2017;Treweek et al, 2018) and one of which involved an autistic stakeholder in reviewing the transcripts(Maloret & Scott, 2018) Jones, Huws & Beck (2013),. involved an autistic panel involved throughout.Enabling and challenging narrativesIn the section above I hope I have demonstrated the ways in which this corpus of work has enabled autistic narratives to emerge more clearly.…”
mentioning
confidence: 99%
“…To date a number of studies have explored how autistic expressions and behavior are perceived by non-autistic people through vignettes and thin-slice judgements (e.g., utilizing video, image, and audio), showing that disclosing a diagnosis of autism significantly improves evaluations (e.g., Chambres et al, 2008; Faso et al, 2014; Brosnan and Mills, 2016). However, reports from autistic people indicate that disclosure of a diagnosis can also result in stigma and negative discrimination (Davidson and Henderson, 2010; Powell and Acker, 2016; Treweek et al, 2018), resulting in a gap in the literature in connecting self-reported perceptions with actual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Autistic reports also indicate that autistic people are misunderstood by non-autistic others resulting in stigma (Dekker, 1999; Chell, 2006; Chown and Beardon, 2017; Treweek et al, 2018). Moreover, media representations have largely focussed on autism as an illness that is a burden to others (Clarke, 2011; Huws and Jones, 2011; Sarrett, 2011; Brownlow et al, 2015), framing autism in terms of a deficit rather than a difference from a neurotypical majority norm (Smukler, 2005; Ortega, 2009; Kapp et al, 2013; Ridout, 2017).…”
Section: Introductionmentioning
confidence: 99%